Spending on public investment and its impact on the reduction of monetary poverty in Peru (2000-2018) - Quiroz Vera, Eduardo Fernando (2020)
The objective of this research was to analyze the impact of public investment spending on the reduction of monetary poverty in Peru for the period 2000-2018, the research is descriptive and explanatory, of correlational design, of longitudinal cut, to quantify the Effects of public investment on poverty, secondary information was used from sources such as the time series of the Central Reserve Bank of Peru and statistics from the Project Bank of the Ministry of Economy and Finance and the National Institute of Statistics and Informatics, the results indicate that public investment spending and poverty levels have an inverse relationship both at the total level and at the level of the sectors that make up the executed public investment, it is concluded that the management of public investment managed to reduce monetary poverty in Peru throughout the study period, being only investment in the social sector that has had a participation significant in reducing poverty.